2002
DOI: 10.1177/154596802401105225
|View full text |Cite
|
Sign up to set email alerts
|

Modified Constraint-Induced Therapy after Subacute Stroke: A Preliminary Study

Abstract: mCIT may be an efficacious method of improving affected arm function and use in stroke patients exhibiting learned nonuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
2
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(98 citation statements)
references
References 8 publications
4
88
2
4
Order By: Relevance
“…4 Numerous studies in stroke patients have shown that CIMT/mCIMT can enhance performance of the affected UE during unilateral and bimanual functional tasks (e.g., flipping a light switch, putting on socks) assessed, for example, using the Motor Activity Log (MAL). [5][6][7][8][9] Bonifer et al 9 reported that CIMT primarily led to improvements in bimanual task performance despite that training was primarily unilateral.…”
Section: Abstract: Cerebrovascular Disease-upper Extremitykinematicsmentioning
confidence: 98%
“…4 Numerous studies in stroke patients have shown that CIMT/mCIMT can enhance performance of the affected UE during unilateral and bimanual functional tasks (e.g., flipping a light switch, putting on socks) assessed, for example, using the Motor Activity Log (MAL). [5][6][7][8][9] Bonifer et al 9 reported that CIMT primarily led to improvements in bimanual task performance despite that training was primarily unilateral.…”
Section: Abstract: Cerebrovascular Disease-upper Extremitykinematicsmentioning
confidence: 98%
“…This could be due to minimal or no learned non-use during the acute phase. However, CIMT was found to be effective in a trial of small sample (n Z 14) of sub-acute stroke (mean Z 4.4-month post stroke) (Page et al, 2002).…”
Section: Constraint-induced Movement Therapy (Cimt)mentioning
confidence: 99%
“…Such evidence leads some to believe repeated practice of ADLs is most critical, rather than the method of practice employed. 7 Despite this suggestion, a further investigation found that 6-h daily CIT produced greater functional benefits than the same therapy lasting just 3 h. 21 Although noted in only 15 patients, two of whom had TBI, it highlights that an optimal duration may exist to bring greatest benefit.…”
Section: Constraint-induced Therapymentioning
confidence: 96%
“…2 CIT is voiced by some as the crux of CVA rehabilitation for the 21st century. 6,7 This set of techniques aims to increase the motor function of the more affected extremity through massed, random practice of ADLs. A minimum of 20°wrist and 10°finger extension prior to treatment are stipulated, with the less affected extremity restrained using a sling or glove.…”
Section: Constraint-induced Therapymentioning
confidence: 99%